Continuum of co-teaching implementation: Moving from traditional student teaching to co-teaching. (August 2017) - Guise, Megan; Habib, Mireille; Thiessen, Krystal; Robbins, Amy
Abstract: This mixed methods study examines the implementation of co-teaching as a model for the teacher education field experience. Participants included eight co-teaching pairs with the goal of determining the extent to which co-teaching occurred, conditions for success, and barriers to implementation. The authors posit that a continuum exists relative to co-teaching implementation with the cooperating teacher's view of his/her role and the purpose of the field experience contributing to where each pair fell on this continuum. This study provides insight into the conditions necessary for coteaching as well as factors that inhibited pairs from moving beyond traditional student teaching. Highlights: Examination of co-teaching implementation by eight pairs during field experience. Existence of a continuum of co-teaching implementation. Community of practice critical for successful co-teaching.